Comparative Analysis of the Factors Affecting the Economic Growth in Georgia and Assessment of the Efficiency of the Budget Policy - Makalatia, Givi (European Scientific Journal, ESJ, 2020)
Correlation among the macroeconomic indicators of Georgia was considered in this article. Also, the predictors of the growth of Gross Domestic Product were revealed. Aim: This paper focuses on defining the role of the state budget among the factors having a significant impact on the increase of the Gross Domestic Product and assessment of the efficiency of the budget policy. Methods: 16 factors affecting the increase of the Gross Domestic Product was studied. Correlations among the factors were defined by means of the Pearson Correlation Analysis. The forecasting factors were assessed by means of the multiple linear regression analysis. In order to verify the degree of the impact of the factors, the regression analysis was carried out in other equal conditions. Results: Linear relation was presented between the state budget and the Gross Domestic Product. Increase in the Gross Domestic Product of Georgia would be defined mostly with the tax revenues into the state budget and afterwards, the direct foreign investments. The state budget, compared with the goods export, facilitates an increase of the service export even more. Conclusions: The main factor affecting economic growth is the tax revenues payable to the state budget. On basis of the regression analysis, it has been revealed that the state budget facilitates an increase of the export of the service even more, compared with the goods export. This preconditions the fact that, in the conditions of the harsh negative foreign trading of Georgia, the efficiency of the budget policy is not high. Chosen priorities, therefore, need to be reviewed. Nowadays priorities include social insurance, social infrastructure, and education.